Regulation of Subunit-Specific Germinal Center B Cell Responses to the HIV-1 Envelope Glycoproteins by Antibody-Mediated Feedback - Forsell, Mattias N. E.; Kvastad, Linda; Sedimbi, Saikiran K.; Andersson, John; Karlsson, Mikael C. I. (Frontiers in Immunology, 2017)
The regulation of germinal center B cell responses to single epitopes is well investigated. How monoclonal B cells are regulated within the polyclonal B cell response to protein antigens is less so. Here, we investigate the primary germinal center B cell response after injection of mice with HIV-1 Envelope glycoproteins. We demonstrate that single germinal centers are seeded by a diverse number of B cell clones shortly after a single immunization and that the presence of Env-specific antibodies can inhibit the development of early germinal center B cells. Importantly, the suppression was dependent on the germinal center B cells and the infused antibodies to target the same subunit of the injected HIV-1 Envelope glycoproteins. An affinity-dependent antibody feedback has previously been shown to regulate germinal center B cell development. Here, we propose that this antibody-based feedback acts on germinal center B cells only if they target the same or overlapping epitopes. This study provides important basic information of germinal center B cell regulation, and for future vaccine designs with aim to elicit neutralizing antibodies against HIV-1.